The Important Role of the Indonesian National Police in Maintaining Security Stability and Its Impact on Indonesia's Economic Growth - Tony Haryono (MultiTech Publisher, 2024)
Security stability is a critical factor influencing economic growth in Indonesia. The Indonesian National Police (POLRI) plays a vital role in maintaining this stability by enforcing laws, preventing and controlling crime, managing emergencies, and supporting business competition. This paper examines the significant impact of POLRI's efforts on Indonesia's economic growth. Through effective law enforcement and collaboration with regulatory bodies like the Business Competition Supervisory Commission (KPPU), POLRI creates a conducive environment for economic activities by ensuring public safety, fostering investor confidence, and supporting fair business practices. Their multifaceted approach, including community policing and securing major events, enhances tourism and investment, driving national economic development. The paper also discusses challenges such as corruption and resource limitations, recommending continued reforms and inter-agency collaboration to sustain and further enhance economic growth.